Implementação de controle servo visual e coordenação visuo-motora em robôs manipuladores - Dâmaso, Renato de Sousa (2006)
This work investigates strategies for controlling a manipulator to approach and grasp an object in its working environment, using visual feedback. Strategies that do not depend on models relating the visual space and the motor space of the manipulator are searched for. Results of the experimental implementations accomplished with an industrial and a prototyped manipulators are presented and analyzed. The main contribution is the proposition of a strategy to experimentally and incrementally build a visuo-motor model to manipulators with binocular visual feedback. Some meaningful characteristics of such a model are the demand of just a few experiments to "learn" the model and the adoption of two data structures to store the estimated parameters, one addressed by the end effector of the manipulator and the other addressed by the position of the object. The model thus obtained can be used to coordinate the manipulator during the execution of the task of interest. Such a system is capable to adapt the visuo-motor model in order to compensate for changes in the manipulator or the visual system, as well as to "remember" information learnt in previous experiments. The method here proposed, the incremental building of the visuo-motor model, is compared to a method of iterative adaptation of Jacobean matrix, and some conclusions are highlighted. As part of such a comparison, results of the implementation of these two methods using the same experimental setup are presented.